Surface wetting of the C/SiC brake lining with micro-scale heat dissipation fins to cool off the brake system: Influence of the fibre ending orientation and fin interval. Issue 14 (1st October 2017) - Wu, M.L.; Ren, C.Z.; Xu, H.Z.; Zhou, C.L.
Abstract: The micro-scale heat dissipation fins significantly contribute to cool off a brake system. However, micro-scale heat dissipation fins will change the surface wetting and then change the humidity of components in the brake system. A higher humidity is helpful for improving the thermal conductivity coefficient of the C/SiC component, which aids in further improving the cooling performance. To the best knowledge of the authors, little attention has been devoted to improving the humidity of the C/SiC brake lining by micro-scale fins. The aim of this study is mainly to discuss the surface wetting of the porous C/SiC brake lining with micro-scale heat dissipation fins to facilitate heat dissipation in the brake system by increasing the humidity. In this study, micro-scale heat dissipation fins with various intervals were fabricated by a laser on three typical C/SiC surfaces. Surface wetting was characterized by the spreading time of the water droplets. The theoretical model of the water droplet spreading time was established by a Washburn-type equation. Both the experimental and theoretical results indicated that: (1) a hydrophilic C/SiC surface could be achieved by fabricating micro-scale heat dissipation fins on a circular fibre-ending surface compared with a pillar fibre-ending surface; (2) wetting control of the C/SiC surface is not obvious by changing of the micro-fin interval on the order of micrometers; and (3) the surface wetting of the pillar fibre-ending C/SiC surface was more sensitive to increased repetitions of laser scanning. In the current stage, the experimental results presented a stochastic surface wetting. In this regard, more details on the irregularity of micro-scale heat dissipation fins resulting from a laser process are discussed. The conclusions can be extended to optimize the heat dissipation fin arrangement of the C/SiC brake lining and optimize the overall cooling performance of the brake system.